Heart Rate Variability During a Joint Attention Task in Toddlers With Autism Spectrum Disorders - Billeci, Lucia; Tonacci, Alessandro; Narzisi, Antonio; Manigrasso, Zaira; Varanini, Maurizio; Fulceri, Francesca; Lattarulo, Caterina; Calderoni, Sara; Muratori, Filippo (Frontiers in Physiology, 2018)
Autism Spectrum Disorders (ASD) are a heterogeneous group of neurodevelopmental disorders featuring early impairments in social domain, with autonomic nervous system (ANS) unbalance possibly representing a useful marker for such disturbances. Impairments in joint attention (JA) are one of the earliest markers of social deficits in ASD. In this study, we assessed the feasibility of using wearable technologies for characterizing the ANS response in ASD toddlers during the presentation of joint attention (JA) stimuli. Twenty ASD toddlers and twenty age- and gender-matched typically developed (TD) children were recorded at baseline and during a JA task through an unobtrusive chest strap for ECG. Specific algorithms for feature extraction, including Heart Rate (HR), Standard Deviation of the Normal-to-Normal Intervals (SDNN), pNNx, Low-to-High Frequency Ratio (LF/HF), and Respiratory Sinus Arrhythmia (RSA) were applied to the ECG signal and a statistical comparison between the two groups was performed. Considering the phase and group interaction, RSAn was not changed from baseline to task among TDs, whereas it was increased among ASDs. Furthermore, the normalized LF signal was increased in both groups during the task, with a greater change among TD subjects (TD: 0.17±0.05 vs 0.23±0.05, p=0.01; ASD: 0.24±0.06 vs 0.28±0.06, p=0.06). As for the single phases, SDNN was increased at baseline in ASD (p=0.020), similarly to pNNx, which was also different (p=0.038), with an increase at baseline in ASD (p=0.045). The results of this study indicate the feasibility of characterizing the ANS response in ASD toddlers through a minimally obtrusive tool, allowing to quantify several parameters related to ANS from the single-lead acquisition of the ECG signal. Our analysis showed an increase of sympathetic activation in ASD, suggesting a possible autonomic dysregulation for the toddlers with such condition here evaluated at baseline. Taken together, such findings foster the application of the proposed approach for evaluating physiological correlates of JA response impairments very early in ASD.